Density and regeneration of mangrove ecosystems in open and natural areas in the waters of Kampung Batu Licin, East Bintan - Mahuris, Aziz; Lestari, Febrianti; Susiana, Susiana; Rochmady, Rochmady (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2025)
Mangroves are vegetation communities that generally grow along the coastline and provide many functions ranging from ecological functions as habitats and economic functions as areas of utilization for humans. In the waters of Batu Licin Village there is an open mangrove area after bauxite mining, therefore it is necessary to conduct research on the level of density and mangrove regeneration seen from the presence of seedlings, saplings, and mangrove trees. This research was conducted in October 2024 in the waters of Kampung Batu Licin East Bintan, the method used in this study is purposive sampling which considers the area around the post-bauxite mine and the area that is still natural. By calculating mangrove density and analyzing the level of regeneration. At the research site found 8 types of mangroves such as Avicenia lanata, Bruguiera gymnorrhiza, Bruguiera cylindrica, Rhizhopora apiculata, Ceriops tagal, Rhizophora mucronata, Xylocarpus granatum, and Sonneratia alba. The density of mangrove seedlings on open land (post bauxite mine) has a high value with a value of 84,000 ind/ha, saplings with a value of 4,960 ind/ha, and trees with a value of 1,310 ind/ha are in the medium category. While on natural land for seedling density with a value of 54,000 ind/ha, at the stake level with a value of 5,240 ind/ha, and trees 1,760 ind/ha are in the very dense category. For the level of regeneration in the two areas is equally good because the presence of seedlings is more than saplings and saplings are more than trees.